Optimization of Liquid Petroleum Gas (LPG) Gas Cylinder Distribution Route with Saving Matrix Method - Fitri Armanda; Rina Filia Sari; Muhammad Dare Garba (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This study aims to optimize the route traveled so that the transportation costs incurred by the company can be much less. This is done because the company as an agent of 3 kg LPG gas cylinders in distributing LPG gas to each base is still not optimal with irregular routes so that the costs incurred by the company are quite large. One solution that can be done in solving this distribution problem is to apply the Saving Matrix method. The Saving Matrix method is one method that can be used to determine the distribution route of a product to the area to be marketed by determining which route to take by looking at the capacity of the vehicle and the number of goods carried in order to get the shortest route and the cost for transportation incurred is small. Based on the results of the study, a distance of 100.73 km was obtained with a total initial distance of 144.29 km, with transportation costs incurred initially of Rp. 98,117.1 to Rp. 68,496.4. So, this shows that the saving matrix method can minimize distance and transportation costs.